Analisis Determinan Kesejahteraan Masyarakat di Kawasan Sarbagita Provinsi Bali dengan Produk Domestik Regional Bruto sebagai Variabel Intervening (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
Community welfare is a key indicator for assessing the success of regional development, particularly in the SARBAGITA metropolitan area, which includes Denpasar, Badung, Gianyar, and Tabanan as the main economic growth centers of Bali Province. Although this region contributes significantly to the provincial economy, disparities in socioeconomic conditions remain evident across districts, influencing the uneven distribution of community welfare. Educational attainment, labor conditions, and changes in the regional economic structure are assumed to be important factors affecting welfare levels. Gross Regional Domestic Product (GRDP) is considered a crucial variable that may mediate the relationship between these factors and community welfare. This study aims to analyze the influence of education and labor on community welfare and to examine the mediating role of GRDP in the SARBAGITA region from 2010 to 2024. The study uses panel data consisting of 60 observations obtained from the Central Bureau of Statistics (BPS) of Bali Province and district-level BPS offices. Data analysis was conducted using path analysis with SPSS version 30. The findings show that education has a positive and significant effect on GRDP, while labor does not significantly affect GRDP. GRDP is found to have a positive and significant impact on community welfare. Education also directly and indirectly influences welfare through GRDP, whereas labor shows no significant direct or indirect effect. These results emphasize the importance of improving education quality and promoting equitable economic growth to enhance community welfare in the SARBAGITA region.